Tip Apex Distance As Predictor of Mechanical Complications in Unstable Intertrochanteric Fractures Treated with Proximal Femoral Nails - Rasheed, Muhammad Asif; Amin, Muhammad Suhail; Chaudhry, Muhammad Nadeem; Haseeb, Malik Muhammad; Muhammad junaid; Naz, Kashif Ali (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the significance of Tip Apex Distance (TAD) as a predictor of mechanical complications in unstable intertrochanteric fractures treated with proximal femoral nails and to ascertain a cut-off TAD value for maintaining stable constructs. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Orthopedics, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 to Aug 2023. Methodology: We assessed patient records for reduction categorized as per baumgartner’s and Chang’s criteria. We evaluated post operative radiographs for TAD and loss of reduction. We reviewed radiological follow ups at 3 months and 6 months to identify mechanical complications. We determined the statistical significance of TAD (p<0.05) and used receiver operating characteristic (ROC) curve to find the sensitive and specific cut-off value for TAD regarding mechanical complications. Results: Among 132 patients, 12(9.09%) experienced mechanical complications. The mean age was 76.3±7.98 years, with 105 males (79.5%) and 27 females (20.5%). The mean TAD was 24.56±2.76 mm, and the mean calcar gap was 5.16±1.27 mm. We found a TAD cut-off of 24.5 mm to be 66.7% sensitive and 51.7% specific for predicting mechanical complications (AUC 0.55). Complications were significant in Cleveland zones: center-center (40.9%), inferior center (49.2%), and inferior posterior (9.9%) (p<0.001). The mean time to full weight-bearing without support was 21.00±1.22 weeks. Conclusion: Maintaining a TAD of less than 25 mm when using the helical blade of intramedullary fixation devices is recommended. TAD is not an independent sole predictor of mechanical complications.